Interaction of monohydrogensulfide with a family of fluorescent pyridoxal-based Zn(ii) receptors. Issue 48 (27th November 2018) - Strianese, Maria; Lamberti, Marina; Pellecchia, Claudio
Abstract : We studied the reactivity of HS − with a family of fluorescent zinc complexes. In the case of complexes1 and3, we have evidence that the interaction with HS − results in the displacement of the coordinated ligand from the Zn center. For complex2, our data points to the coordination of HS − to the metal center likely assisted by hydrogen bondings with the OH of the pyridoxal moiety. Abstract : H2 S and its conjugate base HS − have recently gained increasing attention for their reactivity with bioinorganic targets. However, so far, stable adducts of bioinorganic compounds with H2 S/HS − are still scarce due to the propensity of sulfide to form insoluble metal sulfides. In this work, we studied the reactivity of HS − with a family of fluorescent zinc complexes via a variety of spectroscopic techniques. The complexes selected for this study feature a pyridoxal moiety with different substituent groups on the ligand framework. Interaction of the complexes under investigation with HS − results in the displacement of the coordinated ligand from the Zn center with the concomitant precipitation of ZnS in the case of complexes1 and3, whereas for complex2 our data points to the coordination of HS − to the metal center likely assisted by hydrogen bonding with the OH of the pyridoxal moiety. In the presence of HS −, the fluorescence emission of complex2 is enhanced, whereas the fluorescence emission of complexes1 and3 is quenched. The results highlight the potential of complex2 to be implemented as a HS − fluorescent sensor via a coordinative-based approach.